Comparison of major air freight network hubs in the U.S. and China. (June 2017) - Walcott, Susan M.; Fan, Zhang
Abstract: The increase in global economic connectivity spurred by ties between Chinese manufacturing and a global market, particularly in high value low weight goods, pushed establishment of air cargo networks. These remain under-examined but impactful particularly for second and third tier metropolitan hub cities. This research looks at the air freight connections within China, a major rapidly developing trade center, and use of the aerotropolis concept to accelerate growth in the lagging inland region. References are made to FedEx and UPS networks within their U.S. headquarter region and in China to note differences in political economic contexts and China's adaptation of developed world models. The theoretical framework includes global production networks strategically coupled by transport logistics linked to aerotropolis type development. Data comes from government aviation and transportation sources, research analyses, corporate and industry reports, and interviews with Chinese officials. Focus falls particularly on Zhengzhou, capital of Henan Province in central China and the country's first airport-centered economic zone. The conclusion finds that Chinese hub cities more closely correspond to major manufacturing and population centers and central policy directives for development dispersion. Highlights: Air freight network of FedEx and UPS in U.S and China examined as global connectors. Zhengzhou Airport Economic Zone an aerotropolis exemplar accelerating lagging region. Theoretical frameworks: global commodity networks, strategic coupling; aerotropolis. Data: government statistics, research analyses, industry reports, interviews and site visits. China: manufacturing and population centers, transportation nexus, central policy. U.S.: preferences of corporations, highway connections, local regulations.